Produção de biossurfactante por syncephalastrum racemosum UCP 1302 utilizando substratos agroindustriais e monitoramento computadorizado da temperatura. - Bione, Ana Paula Melo (2019)
Biosurfactants are active surface compounds produced by microorganisms, consisting of a hydrophilic and a hydrophobic portion, with the potential to reduce the surface and interfacial tension of the water and to form emulsions from two-phase liquids, which have received increasing interest in the last decades for the advantages such as biodegradability, low toxicity, production from renewable sources, functionality under extreme conditions of pH and temperature, stability, among others. In this sense, investigations were carried out with Syncephalastrum racemosum UCP 1302 evaluating the ideal temperature for the simultaneous production of biosurfactant and bioemulsifier, using computerized digital monitoring, through the arduino platform and the temperature sensor DS18B20. The bioconversion of renewable residues (residual soybean oil, manipueira and maize) by S. racemosum was studied by applying an experimental design of the DCCR of 23, having as a variable response biosurfactant and / or bioemulsifier production. The results showed that S. racemosum UCP 1302 produced biosurfactant in assay 7 (3.5% maize, 6.5% residual soybean oil and 3.5% mango), reducing the water surface tension of 72 to 30.9 mN / m. The highest production of bioemulsifiers was observed in assay 3 (6.5% of corncine, 6.5% of residual soybean oil and 3.5% of mango), with an emulsification index of 97.58%. The preliminary biochemical composition of the biosurfactant was composed of lipids (53.56%) and proteins (37.88%), with reduced carbohydrate values (8.56%). The bioemulsifier presented proteins (45.72%) and lipids (42.19%), with a low carbohydrate value (12.09%), suggesting that both biosurfactant and bioemulsifante have lipopeptide characteristics. Both biomolecules showed anionic character, with a critical micellar concentration (CMC) of 2,5%. The biomolecules were evaluated for efficiency in terms of particle size, viscosity, stability to pH variations, NaCl concentration and temperature, as well as excellent wetting capacity, indicating a possible applicability to the Improved Oil Recovery (MEOR) process. S. racemosum presented excellent bioemulsifiers production capacity, as well as biosurfactant production capacity, using metabolic conversion of agroindustrial residues, making the bioprocess viable and with potential in the biotechnological application.